Validation of a Malay version of knowledge, attitude, and practice towards safe working in a confined space questionnaire and respiratory health problems among confined space workers of water services industry in the Central Region of Malaysia - Ngah, Hamiza (2022)
Background: Water services industry workers who work in confined spaces (CS) execute a variety of duties, each with its own special hazardous exposures. Working in this type of environment necessitates extreme caution in terms of safety. They could die or suffer from respiratory difficulties as a result of their exposure to potentially dangerous situations in the CS. Objectives: This study aims to develop and validate a Malay version of the knowledge, attitude, and practice toward safe working in a confined space (CS-KAP) questionnaire and to determine the associated factors of respiratory health problems among confined space workers of water services industry in the central region of Malaysia. Methods: This study consists of two phases conducted from April 2020 until December 2021. Phase 1 involved the development and validation of a Malay version of the knowledge, attitude, and practice questionnaire for safe working in a confined space (CS-KAP) among 350 participants from two oil and gas industries in Malaysia. The knowledge component of the validation stage employed two-parameter logistic item response theory (2-PL IRT) analysis, whereas the attitude and practice sections used exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). A cross-sectional study was conducted for Phase 2 among 207 confined space workers working in the water service industry in the central region of Malaysia. A self administered validated CS-KAP questionnaire, an interview guide of the British Medical Research Council (BMRC) and American Thoracic Society (ATS) respiratory symptoms questionnaire, and a pulmonary function test were performed. Hazardous atmosphere gas concentrations (H2S, CO, O2, CH4, and Cl) were collected using a portable multi-gas detector. A descriptive analysis, chi-square, multiple logistic regression, and a general linear regression were performed for the data analysis. Result: The Malay validated CS-KAP questionnaires had good internal consistency reliability. The items in the knowledge section had an adequate level of difficulty and discrimination. Cronbach's alpha values for the attitude and practice sections were 0.804 and 0.917, respectively. Model fitness is high in both sections (Raykov's rho = 0.814 and 0.912, respectively). There was relatively good knowledge (67.1%), a positive attitude (65.7%), and safe practice (60.4%) among CS workers in the water services industry. The presence of chlorine and carbon monoxide gases was detected in a few confined space areas in water treatment facilities. Approximately 45 workers (21.7%) were identified as having at least one respiratory symptom. The proportion of reported phlegm was 27.5%, followed by cough (23.7%), and shortness of breath (13.5%). Respiratory illnesses were associated with the increased frequency of working in CS per year (Adj. OR 0.97; 95% CI: 0.94, 0.99; P = 0.041), lack of training (Adj. OR 0.50; 95% CI: 0.27, 0.92; P = 0.026), and absence of toolbox meetings (Adj. OR 2.53; 95% CI: 1.18, 5.43; P = 0.017). Multiple linear regression revealed that the significant associated factors of pulmonary function were height, age, Malay ethnicity, diastolic blood pressure, obesity, comorbidity, working experience in CS, and knowledge of safe working in CS. Malay ethnicity was associated with an increased in forced vital capacity (FVC) (Adj. b 0.66; 95% CI: 0.34, 0.99; P 0.001) and a decreased in %FEV1/FVC (Adj. b -10.17; 95% CI: -16.00, -4.34; P< 0.001). Height was associated with an increase in forced expiratory volume in one second (FEV1) and FVC (Adj. b 1.55; 95% CI: 0.26, 2.84; P = 0.019; Adj. b 3.57; 95% CI: 2.43, 4.72; P 0.001, respectively). Obesity was positively associated with %FEV1/FVC (Adj. b 3.99; 95% CI: 1.20, 6.79; P= 0.005). Conclusion: The findings suggest that the CS-KAP is a reliable and valid questionnaire for assessing knowledge, attitude, and practice in safe confined space work. Pulmonary function declines and the occurrence of respiratory illnesses indicate that confined space workers in the water service industry are also at risk for chronic exposure to hazardous materials in confined spaces. Safety management and safety hierarchy control should be adopted effectively to provide a safe environmental workplace and lower the impact of respiratory health problems among workers.